The practice of stomatodiabetology in resource-limited settings - Ucheka, Promise Ifeanyi (Orapuh Journal, 2023)
Introduction: Owing to the challenges associated with diabetes care and the ability of its complications to affect multiple organs in the human body, the need for an interdisciplinary approach to diabetes management cannot be over-emphasised. It has been well said that oral health is an essential component of general health and well-being; However, the state of health of the mouth can be influenced by the systemic disease status of an individual. One of the strongest pieces of evidence of this interaction is shown in the bilateral relationship between type two diabetes mellitus and periodontal disease. As a derivative of the practice of stomatology (dentistry) and diabetology (diabetes care), a stomatodiabetologist would be a professional from either profession with prominent or dedicated involvement in collaborative oral health care for diabetes patients.Purpose: This presentation aims to call for interdisciplinarity in diabetes management and to advocate collaborative oral healthcare for people living with type two diabetes.Method: A preliminary search for up-to-date relevant academic literature addressing the oral health-related complications of diabetes using a common risk factor approach and behavioural intervention was conducted.Result:  The published results of this study found some evidence of improvement in both oral health and diabetes status following the introduction of some behavioural intervention as a common risk factor approach to diabetes management.Discussion: Recommendations of the review, to seek the feasibility and acceptability of behavioural interventions in resource-limited healthcare settings such as in Nigeria have been conducted. A mixed methods research design was used as a data collection methods. The preliminary result found that even though up to two third of the patients believed that routine oral hygiene care is an essential part of their diabetes management, more than three-quarters of the patients did not practice routine oral hygiene.Conclusion: In populations where health inequalities are dominant and resources are limited, the practice of stomatodiabetology must be employed as a collaborative tool to manage diabetes mellitus as well as oral health; thereby making every contact count.